Próby integracji środowisk polonijnych w Niemczech w latach dziewięćdziesiątych XX wieku (Świat Idei i Polityki, 2002)
As mentioned in the tittle, the article tries to characterize the integration process of the Polish community in Germany. It describes the problems of the Polish emigrants and their attitude towards the new political and social situation in the nineties. It also highlights the influence of the main legal regulation ”The Treaty of Neighbourly Relationship and Partnership between Poland and Germany” of 17,h June 1991, on the situation of Poles in Germany. The author analyses the stages of the integration process of the Polish people by describing their achievements and defeats. Consequently, it is proved that the lack of unity within the community of Poles is always caused by ”the rule of negation”, as the author calls the phenomenon. Their attitude of disaproval has also a great impact on their social situation and their image on the international scene. It is specially visible among the representatives of new emigrants. In the author'a opinion social status equally depends on the Polish and German authorities, as well as on the active participation of the Polish emigrants. The article ends up with a general conclusion. The author suggests organizing in - depth discussions including all respective representatives of the Polish community in Germany. The outcome should contain current diagnosis of the community and should make suggestions concerning specific actions for Poles living in Germany.